Time Allocation of Reduced Commuting Time During COVID-19 Under Working from Home. (1st October 2022) - Hensher, David; Beck, Matthew; Balbontin, Camila
The COVID-19 pandemic has had a significant impact on weekly commuting activity, with a commensurate increase in remote working, especially from home. The reduction in the amount of commuting time has resulted in time released for other activities. In this paper we identify the incidence of released time to paid work, unpaid work, and leisure, and investigate the key drivers of this allocation. The findings are important in obtaining estimated time benefits from reduced commuting activity with such travel time being traded against work and leisure, and what this might mean for the future travel, activity location, and lifestyle landscape.